Type 1 Narcolepsy in Pregnancy: A Case Report and Review of Literature - Asnat Yuabov; Alexandra Kilinsky; Dina El Kady (Thieme Medical Publishers, Inc., 2024)
Background Type 1 narcolepsy (with cataplexy) is a rare disorder affecting the central nervous system and is characterized by the inability to control sleep-wake cycles. There is a paucity of data regarding management during pregnancy.